An Exploratory Study On Teachers’ Knowledge And Application About The Practice Of Science - Ooi , Hean Beng (2011)
This study explores the teachers’ and trainees’ knowledge about the practice of science and to what extent the said knowledge is shared with their students. Questionnaires were distributed to 139 teachers from Perak, Kedah and Penang and to 110 trainees from one university. Interviews with 13 teachers and 11 trainees were conducted, audio recorded and transcribed. The responses from the questionnaire provided information about the teachers’ knowledge about the practice of science.